2017
DOI: 10.4049/jimmunol.1600310
|View full text |Cite
|
Sign up to set email alerts
|

Novel Adjuvant Based on the Pore-Forming Protein Sticholysin II Encapsulated into Liposomes Effectively Enhances the Antigen-Specific CTL-Mediated Immune Response

Abstract: Vaccine strategies to enhance CD8+ CTL responses remain a current challenge because they should overcome the plasmatic and endosomal membranes for favoring exogenous Ag access to the cytosol of APCs. As a way to avoid this hurdle, sticholysin (St) II, a pore-forming protein from the Caribbean Sea anemone Stichodactyla helianthus, was encapsulated with OVA into liposomes (Lp/OVA/StII) to assess their efficacy to induce a CTL response. OVA-specific CD8+ T cells transferred to mice immunized with Lp/OVA/StII expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 87 publications
(113 reference statements)
1
25
0
Order By: Relevance
“…Previous studies revealed that Sticholysin (St) II, an invertebrate PFP produced by the Caribbean Sea anemone Stichodactyla helianthus belonging to the actinoporin family, was encapsulated into liposome to efficiently enhance the antigen-specific CTL responses as an adjuvant and this may not depend on its pore-forming activity. 64,65 However, βγ-CAT is a vertebrate PFP from the frog B. maxima belonging to the aerolysin family. Importantly, the enhanced antigen presentation induced by βγ-CAT depends on its capacity of pore formation in BMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that Sticholysin (St) II, an invertebrate PFP produced by the Caribbean Sea anemone Stichodactyla helianthus belonging to the actinoporin family, was encapsulated into liposome to efficiently enhance the antigen-specific CTL responses as an adjuvant and this may not depend on its pore-forming activity. 64,65 However, βγ-CAT is a vertebrate PFP from the frog B. maxima belonging to the aerolysin family. Importantly, the enhanced antigen presentation induced by βγ-CAT depends on its capacity of pore formation in BMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Sticholysins I and II (StI and II) are actinoporins produced by the Caribbean Sea anemone Stichodactyla helianthus (23). These toxins are of current interest as an active component of a vaccine platform (24,25) and of immunotoxin constructs active against tumor cells (26,27). Peptides reproducing the N-terminus of StI sequence 1-31 (StI1-31) and StII sequence 1-30 (StII1-30) ( Figure 1A) can mimic the permeabilizing ability of these toxins in red blood cells and liposomes (10,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Its forms pores in human red blood cells with a similar size to those formed by the full-length toxin (9). StII1-30 has emerged as a good candidate to replace the whole toxins in some biomedical applications such as an active component of a vaccinal platform to promote the delivery of different molecules to the cytosol and enhance the immune response in anti-cancer therapies (24,25). Previously, we have analysed the conformational properties of StI1-31 and StII1-30 in solution and in membrane mimetic systems and their ability to permeabilize lipid vesicles (9,12,13,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes, such as those used to target T cells, have shown potential use for immunization and vaccine design due to their ability to transfer and release antigenic molecules in APCs and to stimulate the immune response [145][146][147]. It has been previously reported that StII and StII, toxins from the sea anemone S. helianthus encapsulated in a LP/OVA/StII formulation (mixture of SM-free lipid, ovalbumin and the toxin StII) were used to assess their stimulatory effect on a population of Ag-specific CTLs [43]. This suggests that LP/OVA/StII promotes the expansion of antigen-specific CD8+ T cells compared to that achieved using the liposome formulation that contains only the model antigen (LP/OVA).…”
Section: Actinoporins As An Adjuvant For Vaccine Designmentioning
confidence: 99%
“…Two other possible applications of actinoporins that have been sparsely explored. First, as a component of the design of adjuvant tools for vaccine development, actinoporins could act as immunomodulators to enhance the specific cytotoxic cellular response of antigens within various liposomal formulations that could ultimately be used in the development of vaccines against intracellular pathogens or in cancer [43]. Additionally, because of their preference to bind to sphingomyelin, it has been proposed that actinoporins could be a great molecular tool in the analysis of sphingolipid distribution and dynamics in biological membranes [24].…”
Section: Introductionmentioning
confidence: 99%